Physicochemical characterization and toxicity of nanowaste after incineration process of PA-6/PP/ZnO or TiO2 nanocomposites. Issue 12 (16th November 2022) - Chivas-Joly, C.; Longuet, C.; Leclerc, L.; Sarry, G.; Forest, V.; Lopez-Cuesta, J.-M.; Pourchez, J.
Abstract : Lab-scale incineration process, characterization and toxicity of nanowaste. Abstract : Thermal degradation of PP/PA blends and ternary nanocomposites containing zinc oxide (ZnO) or titanium dioxide (TiO2 ) nanoparticles has been carried out through a lab-scale incineration process. A set up previously validated has enabled to study the fate of resulting nanomaterials in residual ash collected on a grid and soot captured from aerosol. Physicochemical characterizations of these degradation products as well as the pristine nanoparticles were performed using SEM and image analysis, X-micro-analysis, X-rays diffraction, specific surface area and zeta potential measurements. In order to investigate the related hazard through incineration, macrophage cell line was used to evaluate cytotoxicity, pro-inflammatory response and oxidative stress. The use of Pyrolysis-Gas Chromatography coupled with Mass Spectroscopy (Py-GC/MS) showed that the presence of nanoparticles did not modify the decomposition pathway of polymer blends. Besides, ZnO and TiO2 nanoparticles were detected in the residual ash. By contrast, only TiO2 particles were observed in the soot, surrounded by carbonaceous residues and agglomerated with charred structures resulting from polymer degradation. Zeta potential measurements highlighted modifications of isoelectric points of released particles due to charred coating layers. No cytotoxicity was observed for pristine TiO2 and ZnO, whereas pro-inflammatory responses were highlighted. The cytotoxicity and pro-inflammatory responses of soot (in absence or presence of nanoparticles) increased due to the presence of small carbonaceous nanoparticles as well as charred surrounding layers of nanoparticles. The pro-inflammatory profiles of residual ash in presence of nanoparticles indicated a pro-inflammatory response mainly driven by the pro-inflammatory profile of pristine nanoparticles.